ANALISIS OPTIMALISASI PENJUALAN FURNITURE MELALUI LINIER PROGAMMING DENGAN METODE SIMPLEKS PADA PT CAHAYA SAKTI MULTI INTRACO BOGOR - Prasetya, Syarief Gerald (STIE Binaniaga, 2012)
PT. Cahaya Sakti Multi Intraco is a trading company engaged in the procurement of furniture has a variety of types and a variety of brands. In the course of his business face several obstacles in planning the allocation handling products. From one brand alone was encountered problems in the combination of the products offered. Olympic brand is the core product to penetrate the domestic furniture market. Fluctuations in demand for goods erratic from one period to another period resulted in a shortage or oversupplyProducts PT Cahaya Sakti Multi Intraco ie Kitchen Set ( KS ), Cabinet Decorative ( LH ), Wardrobe ( LP ), Desk Study ( MB ) and other furniture products ( OT ). There are several obstacles in the selling of each of these products are: 1 ). The type of vehicle ( truck ) is used to fit furniture consisting of a capacity of 5,500 kgs ( Ants ) , 10,500 kgs ( Elephant ) , 13,500 kgs ( Container 20 ' feet ) , 15,000 kgs ( Double ankle ) , and 27,000 kgs ( Container 40